Information needs of the Lagro Public Library users implications for collection development - Gabor, Henrietta Carla B. (2007)
This study was undertaken for the purpose of determining the information needs of Lagro Public Library users in order to improve the library collection and in turn, better serve its users. This study included a brief evaluation of the current state of the Lagro Public Library and its users. A total of 44 active library users were surveyed using questionnaires. The questionnaires returned by the respondents were compiled and analyzed in accordance with the objectives of the study. Data from these were used to determine the user assessment of the collection and to ultimately identify their needs. The data gathered for the survey questionnaires revealed that the users of the Lagro Public Library have different information needs. The library users mostly need information concerning health, social welfare, career development, sports and recreation and educating/sciences. The study also showed that books are the most used source of information and that majority did not find it hard to obtain needed information from the library. Despite the high level of satisfaction of the library users, a considerable number were not so satisfied because some respondents found it difficult to find what they needed in the library. The library collection still needs improvement.